Transition to remote/hybrid learning during the COVID-19 pandemic among Saudi students of the College of Applied Medical Sciences: a cross-sectional study - Alshamrani, Khalid M.; Ghulam, Enas M.; Alattas, Maryam; Aljaddani, Haneen; Alhakami, Montaha; Al Nufaiei, Ziyad F.; Althaqafy, Majid S. (Frontiers in Medicine, 2023)
The novel Coronavirus Disease 2019 (COVID-19) pandemic has presented unparalleled and unique stressors and challenges to the field of applied health sciences education.This study explored how the College of Applied Medical Sciences (COAMS) Saudi students perceive the transition to remote/ hybrid learning during the COVID-19 pandemic.A cross-sectional exploratory investigation was carried out during the months of February and March in the year 2023 among 196-COAMS Saudi students, using the 48-item previously developed and validated questionnaire, and with a non-probability convenient sampling technique. Descriptive statistics were generated for participants' demographics, and for each questionnaire item and statistical analysis was performed using chi-square test.Results: Out of the 283 undergraduates who have enrolled in COAMS, a total of 196 students have agreed to participate in the study with an overall response rate of 69.3%. Over 70% of COAMS students were satisfied and engaged in their on-site coursework. Nevertheless, questionnaire data indicates that their satisfaction and level of engagement diminished following the shift to remote learning. More than 62% of COAMS students were satisfied with their instructors' instructional and assessment strategies during on-site coursework, but such perceptions have decreased with remote instruction. Hybrid learning can be beneficial and effective in improving the performance and learning experience of COAMS students. As compared to female students, COAMS male students were more satisfied with remote learning because it met their needs (P = 0.017).Remote classrooms have lower attendance and interest than on-site classes. Despite lower satisfaction levels in online courses, hybrid learning was viewed favourably by COAMS students. Higher educational institutions should develop plans to increase student involvement, improve academic integrity, and assess the effect of the pandemic on undergraduate education on a regular basis. By incorporating these measures, educational institutions can enhance and support the remote learning experience for their students.